Computational analysis on flexural behavior of precast aerated concrete panel incorporating polypropylene fiber - Mohamad, Noridah; Lakhiar, Muhammad Tahir; Mansor, Mohamad Syafiq; Koh, Heng Boon; Ahmed Jhatial, Ashfaque; Abdul Samad, Abdul Aziz; Goh, Wan Inn (Science Publishing Corporation, 2018)
Precast system has great advantages in terms of its speed of construction, strength and durability. In this research, Precast Lightweight Aerated Concrete Panel, PACP, incorporating polypropylene fibers were utilized and tested to analyze its structural behavior under flexural load. Finite element analysis (FEA) using LUSAS software was utilized to simulate the PACP models under flexure load adopting nonlinear and transient analysis. The dimension of PACP panel was 200mm thickness, 500mm breadth, 1400 mm length. The FEA results were com-pared to theoretical results in terms of the panel’s ultimate load. Different thicknesses and reinforcement diameters were utilized in the FEM simulations to determine the optimum values for both parameters which confirm the stability of the panel. The outcomes demonstrated that 300 mm thickness is the optimum thickness while 12 mm diameter was the optimum size of reinforcement in the PACP panel.